ASSESSMENT OF GENETIC DIVERSITY AMONG MELON ACCESSIONS USING GRAPHICAL PRINCIPAL COMPONENT AND CLUSTER ANALYSIS - & et al., Naroui Rad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Iran is a part of the secondary center of origin of melons, and therefore, there is a wealth of genetic variation of these species in this country. In this work, 14 morphological traits were studied in order to select the most discriminating traits. Significant difference among accessions was revealed for almost quantitative traits. KMO coefficient obtained was 0.723 that is explaining of appropriation of this test. The results of the principal component analysis (PCA) for the morphological traits indicated that the first three PCs explained 53.46% of the total variation. Principal component analysis results (PCA) for morphometric data indicated that samples of Semnan and Khorasan showed high degree of variation and were highly different from Sistan and this approved by cluster analysis. Cluster analysis grouped the 36 accessions into three clusters confirming the diversity of the collection that can be useful for selection and source of desired genes.